2016
DOI: 10.1016/j.ebiom.2016.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammatory Signaling in the Differential Effects of Saturated and Poly-unsaturated Fatty Acids on Peripheral Circadian Clocks

Abstract: Inflammatory signaling may play a role in high-fat diet (HFD)-related circadian clock disturbances that contribute to systemic metabolic dysregulation. Therefore, palmitate, the prevalent proinflammatory saturated fatty acid (SFA) in HFD and the anti-inflammatory, poly-unsaturated fatty acid (PUFA), docosahexaenoic acid (DHA), were analyzed for effects on circadian timekeeping and inflammatory responses in peripheral clocks. Prolonged palmitate, but not DHA, exposure increased the period of fibroblast Bmal1-dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
5
24
0
Order By: Relevance
“…The period difference observed between the PER2::LUC rhythms in SCN cells (Fig. 4a ) and Bmal1-dluc oscillations in fibroblasts is consistent with our published data [ 34 , 47 ] and reflects differences in cell types and clock gene reporters. In Per2 Luc SCN cells or Bmal1-dLuc fibroblasts treated with 10 μM or 20 μM VX-745, rhythms of bioluminescence persisted for 3–4 cycles similar to the control.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The period difference observed between the PER2::LUC rhythms in SCN cells (Fig. 4a ) and Bmal1-dluc oscillations in fibroblasts is consistent with our published data [ 34 , 47 ] and reflects differences in cell types and clock gene reporters. In Per2 Luc SCN cells or Bmal1-dLuc fibroblasts treated with 10 μM or 20 μM VX-745, rhythms of bioluminescence persisted for 3–4 cycles similar to the control.…”
Section: Resultssupporting
confidence: 92%
“…All DMSO-treated Per2 Luc SCN and Bmal1-dLuc fibroblast cultures exhibited circadian rhythms of bioluminescence that persisted for at least 3–4 cycles with circadian periods of 23.4 h and 25.5 h, respectively. The peak of SCN PER2::LUC expression occurred at ~36 h after the initiation of bioluminescence analysis, and the peak of Bmal1-dLuc in fibroblasts occurred at ~24 h following serum shock, similar to published data [ 34 , 47 ]. The period difference observed between the PER2::LUC rhythms in SCN cells (Fig.…”
Section: Resultssupporting
confidence: 88%
“…CRY protein stability is crucial for defining the pattern of expression of mammalian clock genes ( Zhang et al, 2010 ) and consequently, the destabilization of CRY1 by AMPK affects the overall clock gene expression, notably by promoting CLOCK and BMAL1 expression ( Lamia et al, 2009 ). Indeed, AICAR-induced AMPK activation in fibroblasts induces a phase shift of BMAL1 ( Kim et al, 2016 ). This is potentially part of an important metabolic cross-talk, since AICAR-stimulated glucose uptake in skeletal muscle is reduced in BMAL1 deficient mice ( Harfmann et al, 2016 ).…”
Section: Possible Mechanisms Linking the Clock And Mitochondrial Funcmentioning
confidence: 99%
“…While palmitate is associated with the development of obesity, and Type 2 diabetes, lipotoxicity and oxidative stress, oleate has been shown to prevent or alleviate the toxic effect of saturated free fatty acids and to be protective against insulin resistance and metabolic disorders [27]. Palmitate has been associated with circadian dysregulation in different cell lines [28][29][30][31][32]. In a recent study, non-obesogenic doses of the fatty acids palmitate and oleate showed different effects on circadian rhythms and metabolism both in vitro in hepatocytes and in vivo in mouse liver.…”
Section: Introductionmentioning
confidence: 99%